2021
DOI: 10.1039/d0nr09166a
|View full text |Cite
|
Sign up to set email alerts
|

Hot carriers in graphene – fundamentals and applications

Abstract: Hot charge carriers in graphene exhibit fascinating physical phenomena and have great promise for exciting optoelectronic applications. The current understanding of the relevant fundamental physics and the most promising applications are reviewed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 349 publications
(636 reference statements)
3
105
0
Order By: Relevance
“…We observe that the PC for low LLs does not saturate, whereas the high LL PC saturates much easier. This is consistent with our model since the PC for low LLs is mainly a sum of the electron and hole currents; whereas in the high LL regime the PC saturates much easier since it is the difference of electron and hole currents and thus bottlenecked by the difference of relaxation rates of electrons and holes [25,45]. This is evidenced by the observed markedly different saturation powers, P 0 for low and high LL ( We also see a peculiar double-bent saturation behavior which occurs predominately at high LLs, as shown in the inset of Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observe that the PC for low LLs does not saturate, whereas the high LL PC saturates much easier. This is consistent with our model since the PC for low LLs is mainly a sum of the electron and hole currents; whereas in the high LL regime the PC saturates much easier since it is the difference of electron and hole currents and thus bottlenecked by the difference of relaxation rates of electrons and holes [25,45]. This is evidenced by the observed markedly different saturation powers, P 0 for low and high LL ( We also see a peculiar double-bent saturation behavior which occurs predominately at high LLs, as shown in the inset of Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our work provides an unique study of carrier relaxations using a continuous excitation, which extends beyond the ultrafast regime studied in most pump-probe measurements. We believe our coherent model of PC from graphene in the quantum Hall regime will further the development of applications using graphene such as single-photon detection [46][47][48] and light-harvesting [49,50], as an electrically-measured CM has been longcoveted [25]. The quantum Hall regime can be realized with a synthetic gauge field [51].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 22 , 57 Cooling via diffusion depends on the electronic heat diffusivity D , which increases with charge mobility and Fermi energy. 58 In the case of pump–probe measurements, the observed evolution of the electron temperature increase due to lateral heat diffusion depends on both pump and probe spot sizes (σ pump and σ pr , respectively), according to (see Supporting Information ): Using this equation, we calculate that, for spot sizes below 1 μm, “diffusive cooling” can become the dominant cooling channel in high-mobility graphene samples, even at room temperature. In the measurements we performed on WSe 2 -encapsulated graphene, “diffusive cooling” does not play a large role, due to the relatively large spot sizes that we used (see Figure S12 of the Supporting Information ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have revealed that graphene and CNTs are excellent "hot carriers" emitters (33)(34)(35). It is well known that graphene and CNTs have unique optoelectronic properties due to their Dirac conical and gapless band structure (34,36). This allows them to absorb the laser photons efficiently and easily achieve a population inversion state because of the excitation of hot electrons and the bottleneck of the relaxation at the Dirac point.…”
Section: Resultsmentioning
confidence: 99%